Політична система суспільства : ліберальний проект для України - Телелим, І. В.; Телелим, И. В.; Telelim, І. (My University, 2010)
In the article analyzed evection functioning of domestic administrative structure, and as the most optimum variant is offered and grounded liberal project of functioning of the political system taking into account the real indexes of economic, political and humanitarian development of country of his successful realization.
Телелим І. В. Політична система суспільства : ліберальний проект для України / І. В. Телелим // Актуальні проблеми політики : зб. наук. пр. / редкол. : С. В. Ківалов (голов. ред.), Л. І. Кормич (заст. голов. ред.), Ю. П. Аленін [та ін.] ; МОНмолодьспорт України, НУ ОЮА. - Одеса : Фенікс, 2010. - Вип. 40. - С. 223-233.
Keywords: політична система суспільства; лібералізм суспільства; ефективність функціонування вітчизняної управлінської структури; политическая система общества; либерализм общества; the political system of society; liberalism society; эффективность функционирования отечественной управленческой структуры; the effective functioning of the national management structure